Fuels and ergogenic aids 2.1 - Creatine (1999)
This second issue of Volume 5 of Coaching Science Abstracts (Volume 5(2): October, 1999 FUEL AND ERGOGENIC AIDS 2.1 - CREATINE) reviews 27 articles concerned with creatine use. Previous articles on this topic are contained in Volume 2(3). This issue is divided into the subsections of general theory; strength, power, and size; anaerobic work; repeated anaerobic work; and aerobic work.